Thinwalled structures: analysis of the stressedstrained state and parameter validation - Tkachuk, Mykola; Bondarenko, Maryna; Grabovskiy, Andriy; Sheychenko, Roman; Graborov, Roman; Posohov, Vitaliy; Lunyov, Eugene; Nabokov, Anatoliy; Vasiliev, Anton (Eastern-European Journal of Enterprise Technologies, 2018)
The approach is developed to substantiate technical solutions for thin-walled machine building structures. It implies that the problem is considered in the space of generalized parameters. These parameters combine design and technological factors, as well as operating conditions. In addition, we introduce criterial and constraint dependences to a given space. In the generated uniform parametric space an approximated response surface is constructed, which stretches over a discrete set of solutions to analysis problems. For example, based on the results of examining the stresses-strained state, maximum stresses or displacements, mass or other controlled magnitudes are determined. They are unambiguously computed (a point in a common parametric space) for a specific set of variable generalized parameters. Having a cloud of such points, it is possible to construct an approximated response surface. Approximation constraints are also built on it. Next, by using the methods of nonlinear programming, we search on the set of permissible values for the minimum (or maximum) of quality function of the examined structure. Specifically, for the thin-walled structures, important parameters are the shape and dimensions in a plan, as well as thickness of individual elements. Using a number of structures as examples, authors of present work performed analysis of influence of these parameters on the strength of designed structures.